KARAKTERISTIK MORFOMETRIK KAMBING BOERKA PADA BERBAGAI TINGKATAN UMUR DI UPT. AGRI SCIENCE TECHNOPARK UNISLA - Wenny Ladhunka Nur Aliyya; Muhammad Fathul Amin; Alfian Adi Atma (Wahana Peternakan, 2023)
This study aims to identify the morphometric characteristics of male Boerka goats and female Boerka goats at different age levels as a basic step of selection in breeding and improving the genetic quality of goats. A total of 25 samples of Boerka goats, namely 10 male Boerka goats and 15 female Boerka goats were used to identify qualitative and qualitative traits at the age levels of 0-6 months, >6-12 months, and >12 months. The morphometric parameters observed consisted of qualitative characteristics, namely the diversity of coat colors, the diversity of horn shapes, the diversity of the color of the legs and the diversity of the front lines. While quantitative traits consist of body weight, height, body length, and chest circumference. The results of qualitative research found that Boerka goats had a dominant diversity of brown white fur color, short and small horns, black and white leg color, and a convex head shape. The average values ​​of body weight, height, body length, and chest circumference of male Boerka goats and female Boerka goats at various age levels were not significantly different except for chest circumference with age group > 12 months